Taking Note: A Century of Colonialism in the JCHA/RSHC - Perry, Adele (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
This essay examines the changing place of colonization in the Journal of the Canadian Historical Association/La Revue de la Société historique du Canada and its predecessors. The essay has two aims: to contribute to the discussion of the Canadian Historical Association/Société historique du Canada’s journal on its hundredth anniversary, and to answer Crystal Gail Fraser and Allyson Stevenson’s 2022 call for historians to acknowledge the work of history in legitimating Indigenous dispossession. In the first half-century of the journal’s publication, colonialism was often discussed in celebratory terms, paired with the language of white supremacy or a developmental, colony-to-nation framework. In the second half-century, historians engaged colonialism in more critical terms, including by engaging the analytics of setter colonialism. These changes were uneven, and marked by gaps, contestation, and unease.